Effects of high-intensity interval training on lean mass, strength, and power of the lower limbs in healthy old and young people - Caparrós-Manosalva, Cristian; Garrido-Muñoz, Nicolás; Alvear-Constanzo, Bastián; Sanzana-Laurié, Sofía; Artigas-Arias, Macarena; Alegría-Molina, Andrea; Vidal-Seguel, Nicolás; Espinoza-Araneda, Jessica; Huard, Nolberto; Pagnussat, Aline Souza; Sapunar, Jorge; Salazar, Luis A.; et al. (Frontiers in Physiology, 2023)
Introduction: Whether HIIT can improve lean mass, strength, and power in both legs of young and older people is still under discussion. This study aimed to determine the effect of HIIT on lean mass, maximal strength, rate of strength development (RFD), and muscle power of both lower limbs in healthy young and older adults. Secondarily, to compare the effects of HIIT between dominant vs non-dominant lower limbs of each group. Materials and methods: Healthy older (n=9; 66±6 years; BMI 27.1±3.1 kg·m-2) and young (n=9; 21±1 years; BMI 26.2±2.8 kg·m-2) men underwent 12 weeks of HIIT (3x/week) on a stationary bicycle. The evaluations were made before and after the HIIT program by dual energy X-ray absorptiometry (DEXA), circumference anthropometry, force transducer and, Sit-to-Stand test. The outcomes analyzed were limb lean mass, thigh circumference, maximal voluntary isometric strength, RFD (Time intervals: 0-50ms, 50-100ms, 100-200ms, and 0-200ms), and muscle power in both lower limbs. Results: After 12 weeks of HIIT, NDL showed increase in limb lean mass (P<0.05) but without interaction. HIIT showed a gain in maximal strength and when adjusted for thigh circumference in the dominant lower limb (DL) in both groups, with differences to the non-dominant limb (NDL) (P < 0.05) but without time*group effects (P>0.05). The RFD0-200 ms showed differences between groups but without interaction. The RFD0-50 ms of the NDL showed post-training improvements (P<0.05) in both groups. Only the older group showed differences between DL vs NDL in most of the RFD obtained post-intervention. In addition, post-HIIT muscle power gain was observed in both groups (P<0.05), but mainly in older adults. Conclusion: HIIT promotes increases in lean mass, maximal strength, early RFD, and lower limb muscle power in healthy older and young individuals. The differences shown between the DL and the NDL must be analyzed in future studies.